2010
DOI: 10.1016/j.foodpol.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of off-farm income on food security and nutrition in Nigeria

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
188
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 331 publications
(248 citation statements)
references
References 19 publications
24
188
1
5
Order By: Relevance
“…This is consistent with the idea in the broader development literature that labour market development and off-farm employment is important for rural development (Barrett et al, 2001;Haggblade et al, 2010;Lanjouw and Lanjouw, 2001). Empirical studies from various countries have shown that off-farm income in general, and wages in particular, increase rural incomes (Cramer et al, 2008;Oya, 2013;Rizzo et al, 2015); and that non-farm work has a positive effect on nutrition and food security (Babatunde and Qaim, 2010;Owusu et al, 2011). Our study adds to this evidence but also contradicts it to some extent.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the idea in the broader development literature that labour market development and off-farm employment is important for rural development (Barrett et al, 2001;Haggblade et al, 2010;Lanjouw and Lanjouw, 2001). Empirical studies from various countries have shown that off-farm income in general, and wages in particular, increase rural incomes (Cramer et al, 2008;Oya, 2013;Rizzo et al, 2015); and that non-farm work has a positive effect on nutrition and food security (Babatunde and Qaim, 2010;Owusu et al, 2011). Our study adds to this evidence but also contradicts it to some extent.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, some define food security as the success of local livelihoods in guaranteeing access to sufficient food at the household level (Devereux and Maxwell 2001). The focus of household-level food security research is to study the strategies used by people to achieve food security, whether it be migration (Karamba et al 2011), income diversification (Babatunde and Qaim 2010), or the use of technology (Burney and Naylor 2012), for example. Food security can be seen as one dimension of a broader livelihood strategy (Maxwell and Smith 1992).…”
Section: Food Security and Livelihoodsmentioning
confidence: 99%
“…This is partly related to complexities in terms of measuring food insecurity (Barrett, 2010;Webb et al, 2006). The most common measurement approaches at the micro level build on dietary recalls, anthropometric indicators, or health data, which have also been used for impact assessment in a few studies (Babatunde and Qaim, 2010;Ecker and Qaim, 2010;Haddad et al, 1998;Rusike et al, 2010). There are also studies that try to measure food insecurity through data on household coping strategies (Maxwell et al, 1999;Maxwell et al, 2008).…”
Section: The Household Food Insecurity Access Scale (Hfias)mentioning
confidence: 99%